AUDIT REPORT LAG KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2020-2024 - Minawati, Minawati; Malahayati, Rina; Jamaris, Edi (LPPM Universitas Putera Batam, 2025)
The late publication of a company's financial report is known as Audit Report Lag. Timeliness in submitting financial reports is crucial and is governed by various official regulations. This should encourage public companies to report their financial statements on time. The purpose of this study is to determine and analyze the effect of Financial Audit Report Lag on Manufacturing Companies Listed on the IDX in 2020-2025. This research uses a quantitative approach. The sampling technique used in this study is a census method or saturated sampling, where the entire population is used as a sample. Therefore, the total population used in this study is 12 Manufacturing Companies in the Food and Beverage Subsector x 5 years = 60 data. The type of data used in this study is quantitative data with secondary data sources, namely company financial reports. The collected data were tested using descriptive statistics, classical assumption tests, multiple linear regression, and simultaneous and partial hypothesis testing using SPSS software. Profitability partially had a positive and significant effect on audit report lag. Solvency partially had a negative and significant effect on audit report lag. Company size partially had a positive and significant effect on audit report lag. Profitability, solvency, and company size simultaneously had a positive and significant effect on audit report lag. Variations in the variables Profitability, solvency, and company size explained 52.5% of their effect on audit report lag, while the remaining 47,5% was due to variations in other variables not explained in this study, such as cash flow, etc.